Inhibition of Cell Growth and Shoot Development by a Specific Nucleotide Sequence in a Noncoding Viroid RNA - Qi, Yijun (American Society of Plant Biologists, 2003)
Viroids are small noncoding and infectious RNAs that replicate autonomously and move systemically throughout an infected plant. The RNAs of the family Pospiviroidae contain a central conserved region (CCR) that has long been thought to be involved in replication. Here, we report that the CCR of Potato spindle tuber viroid (PSTVd) also plays a role in pathogenicity. A U257A change in the CCR converted the intermediate strain PSTVd(Int) to a lethal strain that caused severe growth stunting and premature death of infected plants. PSTVd with nucleotide U257 changed to C or G did not cause such symptoms. The pathogenic effect of the U257A substitution was abolished by a C259U substitution in the same RNA. Analyses of the pathogenic effects of the U257A substitution in three other PSTVd variants established A257 as a new pathogenicity determinant that functions independently and synergistically with the classic pathogenicity domain. The U257A substitution did not alter PSTVd secondary structure, replication levels, or tissue tropism. The stunted growth of PSTVd(Int)U257A-infected tomato plants resulted from restricted cell expansion but not cell division or differentiation. This was correlated positively with the downregulated expression of an expansin gene, LeExp2. Our results demonstrate that specific nucleotides in a noncoding, pathogenic RNA have a profound effect in altering distinct cellular responses, which then lead to well-defined alterations in plant growth and developmental patterns. The feasibility of correlating viroid RNA sequence/structure with the altered expression of specific host genes, cellular processes, and developmental patterns makes viroid infection a valuable system in which to investigate host factors for symptom expression and perhaps also to characterize the mechanisms of RNA regulation of gene expression in plants.